(untitled) (Open Herald: Periodical of Methodical Research, 2024)
The purpose of the study to investigate the causes of cardiovascular diseases when the components of a healthy lifestyle, the rules of rational and rational nutrition, the hygienic norms of basic food substances and nutrients are violated,harmful habits: not following the principles of correct and rational nutrition, excessive consumption of doughy food and sweets, bread products with a large amount of salt, sugar and fat, not observing the diet and eating before bedtimestudy that it is one of the main causes of cardiovascular diseases.